Poetics of algorithmic excess: digital aesthetics in Indonesia’s Twitter poetry bot - Yahya Auliya Abdillah (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2026)
Background: The rapid expansion of social media platforms has transformed literary production, enabling algorithmic poetry to emerge as a digital-native form that challenges conventional notions of authorship, meaning, and aesthetic value. Objective: This study examines how Indonesian Twitter bot poetry operates as a poetics of algorithmic excess, with attention to formal patterns, semantic instability, and platform-mediated authorship. Method: Using a qualitative digital humanities approach, the research analyzes a corpus of 240 poems generated by an Indonesian Twitter poetry bot through close reading, pattern identification, and platform-aware interpretation. Results: The findings show that algorithmic repetition and structural fragmentation function as dominant formal strategies, displacing expressive intentionality with procedural regularity. Semantic noise and randomness produce episodic meaning, shifting interpretive responsibility from author to reader. Platform circulation redistributes authorship among algorithms, users, and infrastructural systems, positioning Twitter/X as a co-author in literary production. Implications: Algorithmic poetry constitutes a legitimate literary practice shaped by platform capitalism and posthuman creativity. Novelty: The study offers a Global South perspective on digital poetics by theorizing algorithmic excess as an aesthetic principle within platform-mediated literature.